Pedunculated Angiomyofibroblastoma of the Vulva: Case Report and Review of the Literature - Luca Giannella; Matteo Costantini; Kabala Mfuta; Alberto Cavazza; Lillo Bruno Cerami; Giorgio Gardini; Fausto Boselli (Case Reports in Medicine)
Angiomyofibroblastoma (AMFB) is a rare benign mesenchymal tumour that occurs almost exclusively in the vulvovaginal region of women but can also occur occasionally in the inguinoscrotal region of men. It is a well-circumscribed lesion that clinically is often thought to represent a Bartholin's gland cyst and usually does not form a pedunculated mass. To our knowledge, only five cases of vulvar AMFB with pedunculated mass have been reported in the English literature and all cases involving the labia majora and middle-aged women. We report the first case of pedunculated AMFB of the vulva occurring in a young woman of 21 years old and involving the left labia minora. After excluding the most common diseases, pedunculated AMFB should be part of differential diagnosis in the workup of any pedunculated vulvar mass even in young women with a lesion involving the labia minora. We reviewed the literature and summarized all reported cases.